2020
DOI: 10.14202/vetworld.2020.317-325
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antibiogram of Listeria species in raw pork, beef, and chicken meats marketed in Enugu State, Southeast Nigeria

Abstract: Aim: This study was undertaken to isolate Listeria (L.) species from raw meats sold in markets in Enugu State, Southeast Nigeria, and to determine the antibacterial resistance profile. Materials and Methods: Twenty-five grams of beef (n=144), chicken meat (n=144), and pork (n=144) were collected randomly from supermarkets and general markets in Enugu State. Isolation of Listeria was done using half and full Fraser broths, and polymyxin acriflavine lithium chloride ceftazidime aesculin mannitol agar. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Our findings reiterate cattle as an important carrier of L. monocytogenes and agree with previous reports that this foodborne pathogen is quite prevalent in animals and their products [9,30,38]. More specifically, this study demon strated that cow faeces and foetuses remained a potential source of L. monocytogenes infection to meat processors and handlers.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings reiterate cattle as an important carrier of L. monocytogenes and agree with previous reports that this foodborne pathogen is quite prevalent in animals and their products [9,30,38]. More specifically, this study demon strated that cow faeces and foetuses remained a potential source of L. monocytogenes infection to meat processors and handlers.…”
Section: Discussionsupporting
confidence: 92%
“… 432 28.7 [ 12 ] Nigeria Raw meat and meat product Listeria spp . 300 28.3 [ 13 ] Nigeria Salad vegetables, Salad and coleslaw L. monocytogenes 355 3.9 [ 14 ] Nigeria Cabbage/Carrot/Cucumber/Lettuce/ Tomatoes L. monocytogenes 555 44.0 [ 15 ] Nigeria Soft cheese L. monocytogenes 116 49.1 [ 12 ] Nigeria Raw beef, pork and chicken L. monocytogenes 205 7.8 [ 16 ] Nigeria Raw beef and chevon L. monocytogenes 104 64.4 [ 5 ] Ghana Raw cow milk/Nunu/Boiled milk L. monocytogenes 254 5.5 [ 17 ] Ethiopia Beef, butchers and restaurant L. monocytogenes 450 4.4 [ 18 ] Ethiopia Pizza, cake, ice cream, minced beef, fish, raw meat, and unpasteurized milk L. monocytogenes 384 6.3 [ 19 ] Ethiopia Vaginal samples of pregnant women L. monocytogenes 141 8.5 [ 20 ] Botswana Cheese, raw milk, meat (biltong), frozen cabbage and salad L. monocytogenes 1324 4.3 [ ...…”
Section: Epidemiologymentioning
confidence: 99%
“…In Enugu state, Nigeria, the frequency of Listeria spp. isolated from chicken meat, pork, and beef samples was 27.1, 13.2 and 45.8% respectively [ 12 ], while in Zaria, Nigeria, the prevalence of L. monocytogenes in raw meat and meat products was 4.0% [ 13 ]. Other studies in Nigeria reported the prevalence of L. monocytogenes in vegetables including in cabbage, carrot, cucumber, lettuce, and tomatoes to be, 28.28, 9.02, 23.36, 19.67, and 19.67%, respectively [ 15 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiotic sensitivity profile of Listeria spp., however, varies with the use of drugs in human and veterinary medicine in different geographical areas. Inappropriate use of antibacterial drugs is the major cause of acquired resistance in Listeria species [4]. Multiple drug resistance in L. monocytogenes strains isolated from fish, raw and ready-to-eat seafood product samples has been reported [5].…”
Section: Introductionmentioning
confidence: 99%